The Majoritarian Threat to Liberal Democracy. Issue 1 (29th January 2022) - Grossman, Guy; Kronick, Dorothy; Levendusky, Matthew; Meredith, Marc
Abstract: Incumbents often seek to wield power in ways that are formally legal but informally proscribed. Why do voters endorse these power grabs? Prior literature focuses on polarization. We propose instead that many voters are majoritarian, in that they view popularly elected leaders' actions as inherently democratic – even when those actions undermine liberal democracy. We find support for this claim in two original survey experiments, arguing that majoritarians' desire to give wide latitude to elected officials is an important but understudied threat to liberal democracy in the United States.